BIONANOSCULP, an ongoing project in biotechnology applications for preventive conservation of outdoor sculptures - Moreira, P. R. (2019)
The objective of this paper is the presentation of the research strategies adopted and results of the ongoing BIONANOSCULP research project that is aiming to develop solutions in the area of sustainable nanomaterials, which are non-invasive and high-performance in their preventive conservation approach. An integrated methodology was designed as a holistic strategy to the characterisation of the microbiota present on the surface of public outdoor sculptures. Gathering objective data in the characterization of the surface microbiota of public outdoor sculptures is important, in order to design strategies for the preventive conservation of these objects that make use of biotechnology innovative coatings. Such is one of the objectives of the project BIONANOSCULP. Methodologies applied include conservation reports, surface sampling methodologies using gels, 3D modeling, SEM, flow cytometry and metagenomics. The project is already significantly contributing to create a bridge between the experts from different areas: the skills of biotechnologists, microbiologists, materials scientists, art historians and conservators-restorers to assess the state of conservation, biodeterioration and biocontamination of a selected number of sculptures, and to design the appropriate materials to pursue preventive conservation through coatings with anti-microbial activities.